Do sanctions reduce the military spending in Iran? - Sajjad Faraji Dizaji; Mohammad Reza Farzanegan (Philipps-University Marburg, School of Business and Economics, 2018)
This study focuses on short and long-term effects of sanctions on military spending in Iran. Utilizing the annual data from 1960 to 2017 and the auto regressive distributed lag (ARDL) model, we show that the increasing intensity of sanctions dampen the military budget of Iran. By separating unilateral sanctions (where only the United States sanctions Iran) and multilateral sanctions (where, the United States acts in conjunction with other countries to sanction Iran), we show that only the latter class of sanctions have a statistically significant and negative impact on military spending of Iran. The negative effects of the multilateral sanctions on military budget are observed in both the short and long run time horizons. The results remain robust when controlling for other determinants of military spending such as gross domestic product (GDP), oil rents, trade openness, population, quality of political institutions, military expenditure of the Middle East region, non-military spending of government and the war period with Iraq.
Keywords: 330; sanctions; military spending; Iran; ARDL